Hand gesture recognition system using image processing (2007)
Image processing has a very big potential to do virtually anything. But in real life, worse come to worst when the development of particular interest is not being done properly. This project comes to the extent of development details on recognition system by using state-of-the-art NI LabVIEW graphical programming software. The complexness and configurable in so many way of today’s entertainment has brought us back to basic of safety. It is worthless to have a complete system that can do almost anything but compromises human life. To cope up on par to today technological achievement, this project will try to bring sophisticated ways of using image processing as a solution to deliver command in the other way. The hardware is being interfaced by using Software Development Kit (SDK) from the supplier of the hardware, in this case is Logitech Inc. Proper data channeling between hardware and software ensure smooth transaction that increase performance and capability. The method of backlighting is used to give proper exposure to the subject so that the further processing and blob (binary large object) analysis can be done on it. This system also used algorithm of several processing technique that may or may not be the same output for each type of it. The system is upgradeable to be connected by separate module. It will not be viable to implement it today, but the ever falling prices of gadget plus a little bit of innovation into infrared lighting, 0 lux night vision acquisition, refine image processing and fuzzy logic to keep the system trained, it will be everyday must. This is proven, considering costly research and development on Air Bag technology as an example, sometimes ago is now a necessity.